Development of Switching Intention Model of Hotel Industry in Bandung - Prihartono, Budi; Monika, Fika Endah; Prasetyo, Ilham Reza (RSF Conference Series: Business, Management and Social Sciences, 2022)
Switching intention in the hospitality industry is shaped by various factors, including service performance, customer satisfaction, and switching barriers. The hospitality industry itself cannot be separated from the loyalty program as it is one of the most common tools used in managing customer behavior. Therefore, this study will analyze the factor of loyalty program towards switching intention. The switching intention model in this study is formed by main service performance, service encounter performance, customer satisfaction, switching barriers, and loyalty programs. The data analysis performed in this research is multigroup structural equation modeling. The grouping of the samples is divided based on the type of hotel visited by the respondents, which are luxury hotels and medium to low hotels. Luxury hotels consist of 4-5 star hotels, while medium to low hotels consist of 1-3 star hotels. The sample size used is 250 respondents with analysis performed using MPlus. The results confirm that loyalty program, along with main service performance and service encounter performance influences switching intention. Based on the result, it is also found that different group of customers also have different effect on the relationship in the model.